Place-based Leadership in a Global Era (Commonwealth Journal of Local Governance, 2011)
This article examines the major challenges now facing local governments across the world and advocates the development of a new focus on place-based leadership for local government scholarship and practice. The challenges facing local authorities are many, but they can be summarised in two words: globalisation and urbanisation. In response to these we have witnessed, in many countries, a shift from ‘local government’ to ‘local governance’. This shift is discussed, and it is suggested that new models of partnership working could, if handled in the wrong way, undermine local democracy. To combat this danger it is essential to give civic leadership far more attention – in the worlds of both academe and practice. A new way of conceptualising place-based leadership – one that identifies three ‘realms of civic leadership’ – is put forward. This model emphasises the role of civic leadership in shaping emotions and supporting public service innovation. To illustrate the argument an example of highly respected place-based leadership is presented. Freiburg, Germany is recognised as a very successful eco-city and the leadership model is used to help explain why. The article concludes with some reflections and pointers for research and policy. It is suggested that new forms of ‘engaged scholarship’ – approaches that bring together academics and practitioners to co-produce new knowledge about place-based leadership in an international, comparative perspective – should be encouraged.